“Colorectal Cancer Care Quality in a Developing Country: Insights from a Comparison of Teaching and Non-teaching Hospitals in Iran” - Mohammad Reza Rouhollahi; Mahdi Aghili; Saeed Nemati; Mohammad Ali Mohagheghi; Farid Azmoudeh Ardalan; Habibollah Mahmoodzadeh; Mehrzad Mirzania; Mohammad Shirkhoda; Seyed Hossein Yahyazadeh; Ahad Muhammadnejad; Sepideh Abdi; Maedeh Zokaei Nikoo; et al. (PLoS ONE, 2025)
Background Our study represents the first effort in the Eastern Mediterranean Region to identify disparities in the quality of colorectal cancer (CRC) care in Iran. Methods We established a collaborative registry program for non-metastatic CRC patients to evaluate survival rates between teaching cancer centers (TCCs) and a high-volume, non-teaching, non-cancer center (NTNC). The study included a diverse patient population and considered various factors such as cancer stage, margin involvement, adherence to guidelines for adjuvant and neoadjuvant treatments, emergency surgeries, socioeconomic status, and risk of surgery. We utilized a multivariate Cox regression model and the targeted maximum likelihood estimator (TMLE) to analyze survival disparities in colorectal cancer between TCCs and the NTNC. Results We recruited 668 CRC patients, including 320 with colon cancer and 298 with rectal cancer. Patients who underwent surgery at teaching cancer centers (TCCs) displayed significantly higher quality of care and better outcomes than those treated at the non-teaching, non-cancer center (NTNC). The adjusted hazard ratios (HR) were 1.97 (95% CI 1.21–3.21) for colon cancer and 1.54 (95% CI 1.01–2.55) for rectal cancer. Additionally, we observed significant causal mortality risk ratios (RR) based on hospital type for overall colorectal cancer (RR = 1.42, 95% CI 1.12–1.81) and specifically for colon (RR = 1.48, 95% CI 1.04–2.11) and rectum cancer (RR = 1.39, 95% CI 1.01–2.02). Conclusion The survival disparities in colon and rectal cancers between TCCs and NTNCs highlight a significant gap in CRC care in Iran. It is essential to expand this study nationally and implement the knowledge and experiences from TCCs in other hospitals to improve the quality of care and enhance patient outcomes.